Draft Third Five-Year Plan Bihar Vol. II Statistical Appendices - Planning Commission (Planning Commission, 1960)
This Project envisages construction of river Karaikal not Rungel-Beru in the district of Singh hum. the catchment area at the dam Kite will be 1,100 square miles and the proposed will irrigate 50,000 acres of kharif crop. The catchment cost is Rs. 2 crores and the incidence of cost will be Rs. 400 per acre.
Bihar